(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
In this paper, we present an analysis of the opinions and attitudes of teachers of Spanish as a foreign language in Serbia towards the concept of hidden curriculum and the way they define it, with special reference to the gender-sensitive approach in teaching. The questionnaire was forwarded to the respondents electronically. After a qualitative analysis, we came to the results that indicate that the teaching staff defines the implicit curriculum in different ways and does not attach the same importance to it, forgetting that the school not only serves to transfer knowledge, but actively participates in shaping gender and other identities. and gender ideologies, which are also the basic theoretical postulates of critical pedagogy on whose ideas this work is based.